Establishing a combined forecasting model: a case study on the logistic demand of Nanjing’s green tea industry in China - Lin, Hung-Lung; Lin, Chin-Tsai (Technological and Economic Development of Economy, 2021)
The sales logistics of tea leaves is a process that organically integrates basic logistics activities, including transportation, storage, loading, unloading, carrying, packaging, distribution processing, delivery, and information processing. This process requires quick and accurate forecasting of the logistics demand in the green tea market and the provision of feedback to businesses and farming partners, revealing the need for a simple and accurate forecasting method. Responding to and solving the unclear information and limited data available regarding the green tea market are critical. Therefore, this study established a simple, quick, and accurate model through the use of time series and the technique for ordering preferences by similarity to the ideal solution. Finally, the actual logistics demand in the Nanjing green tea industry was employed to verify the proposed model’s practicality and feasibility, which may provide a critical reference for relevant parties such as businesses and researchers.First published online 14 December 2020